Asymptotic Inference in the Lee-Carter Model for Modelling Mortality Rates - Simon Reese (Lund University, School of Economics and Management, Department of Economics, 2015)
The most popular approach to modelling and forecasting mortality rates is the model of Lee and Carter (Modeling and Forecasting U. S. Mortality, Journal of the American Statistical Association, 87, 659–671, 1992). The popularity of the model rests mainly on its good fit to the data, its theoretical properties being obscure. The present paper provides asymptotic results for the Lee-Carter model and illustrates its inherent weaknesses formally. Requirements on the underlying data are established and variance estimators are presented in order to allow hypothesis testing and the computation of confidence intervals.
Keywords: C33; C51; C53; J11; 330; Lee-Carter model; mortality; common factor models; panel data